2022
DOI: 10.21203/rs.3.rs-2078757/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to the Family Wellbeing program and associations with empowerment, health, family and cultural wellbeing outcomes for Aboriginal and Torres Strait Islander peoples: A cross-sectional analysis

Abstract: Background: Empowerment is a concept commonly incorporated into Aboriginal and Torres Strait Islander health and wellbeing programs. The Family Wellbeing Program is an empowerment program developed in partnership with Aboriginal and Torres Strait Islander peoples that has been widely delivered to Aboriginal and Torres Strait Islander communities across Australia for close to 30 years. To date, there has been limited quantitative analysis of how this program may be linked to health and empowerment outcomes. Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 22 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…A further source of relevant data involved the Mayi Kuwayu National Study of Aboriginal and Torres Strait Islander Wellbeing. Over the past five years, analysis of data obtained through this study reinforced the small-scale research findings by indicating robust associations between Family Wellbeing exposure and empowerment outcomes (Williamson et al, 2023). The study uses a culturally congruent survey designed in collaboration with Aboriginal and Torres Strait Islander communities across Australia.…”
Section: Box 1: Notable Yarrabah Stories Of Transformation and Changesupporting
confidence: 64%
See 3 more Smart Citations
“…A further source of relevant data involved the Mayi Kuwayu National Study of Aboriginal and Torres Strait Islander Wellbeing. Over the past five years, analysis of data obtained through this study reinforced the small-scale research findings by indicating robust associations between Family Wellbeing exposure and empowerment outcomes (Williamson et al, 2023). The study uses a culturally congruent survey designed in collaboration with Aboriginal and Torres Strait Islander communities across Australia.…”
Section: Box 1: Notable Yarrabah Stories Of Transformation and Changesupporting
confidence: 64%
“…The analysis concluded that there are strong associations between Family Wellbeing exposure and empowerment outcomes at the family and community levels. For example, compared to non-participants, Aboriginal and Torres Strait Islander participants in Family Wellbeing reported:• a 13% higher rate of family functionality• a 74% higher rate in higher cultural wellbeing• a 21% higher rate in higher levels of local decision-making in community (Williamson et al, 2023). …”
Section: Box 1: Notable Yarrabah Stories Of Transformation and Changementioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, population-wide programmes, including Family Well-being Programmes, Childcare and Early Education, and Child Welfare Programmes, have been implemented for approximately three decades, targeting the general population. The Family Well-being programme has been tested among Indigenous communities and shown to have positive effects on preventing family violence and improving school attendance rates, as well as health behaviours, including reduced rates of smoking, heavy drinking and substance use 29. However, evaluation of social security programmes including financial assistance (JobSeeker Payment, Child Support Scheme) has had mixed benefit in the Northern Territory 30.…”
Section: Will Aces Prevention Help Close the Gap?mentioning
confidence: 99%